“Germany for Germans:” Examining the social media use of two major political parties in Germany - Caffera, Catherine (My University, 2017)
Overview of findings from an undergraduate research project into the use of social media by the Christliche Demokratische Union (CDU) and Alternativ für Deutschland (AfD) between December 1, 2016 and March 20, 2017. The project focuses on the use of language, content and images of social media posts on Facebook and Twitter by each party.
Citation: Caffera, C. (2017). “Germany for Germans:” Examining the social media use of two major political parties in Germany. Initials: Student Research Forum, April 21, 2017. Manhattan, KS.
Keywords: Germany; Social Media; Facebook; Twitter; Politics; Communication